Advances in big data : proceedings of the 2nd INNS Conference on Big Data, October 23-25, 2016, Thessaloniki, Greece - Angelov, Plamen P.; Manolopoulos, Yannis, 1957-; Iliadis, Lazaros S.; Roy, Asim; Vellasco, Marley Maria B. R. (Springer, 2017)
The book offers a timely snapshot of neural network technologies as a significant component of big data analytics platforms. It promotes new advances and research directions in efficient and innovative algorithmic approaches to analyzing big data (e.g. deep networks, nature-inspired and brain-inspired algorithms); implementations on different computing platforms (e.g. neuromorphic, graphics processing units (GPUs), clouds, clusters); and big data analytics applications to solve real-world problems (e.g. weather prediction, transportation, energy management). The book, which reports on the second edition of the INNS Conference on Big Data, held on October 23-25, 2016, in Thessaloniki, Greece, depicts an interesting collaborative adventure of neural networks with big data and other learning technologies.
International conference proceedings.
Keywords: Big data -- Congresses.; elektronické knihy; electronic books